Effects of the bubbles in slag on slag flow and heat transfer in the membrane wall entrained-flow gasifier. (5th February 2017) - Zhang, Binbin; Shen, Zhongjie; Han, Dong; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: The slag flow and heat transfer model were modified with the bubbles in slag. The bubbles in slag reduced the slag thermal conductivity and viscosity. The bubbles in slag increased the liquid slag velocity. The bubbles in slag reduced the liquid and solid slag layer thickness. The bubbles in slag reduced the slag heat flux. Abstract: The slag from the industrial gasifier has porous structure, which has a non-ignorable influence on the characteristics of slag layer. The slag flow and heat transfer model were modified based on the effective thermal conductivity and viscosity, to predict the slag characteristics for the effects of bubbles in slag. The results show that bubbles inside slag reduce the slag thermal conductivity and viscosity. The modified model predicts the liquid slag velocity, slag layer thickness and heat flux of slag layer. The liquid slag flow velocity increases with the increase of bubbles inside slag, while the thickness of slag layer decreases. In addition, the increasing gas volume fraction of bubbles inside slag decreases the heat flux of slag layer. Two models are applied to calculate the bubbly slag effective thermal conductivity. The Maxwell-Eucken thermal conductivity model is more accurate than geometric mean model from the result of slag layer heat flux.